Comprehensive metabolite profiling of Plantaginis Semen using ultra high performance liquid chromatography with electrospray ionization quadrupole time‐of‐flight tandem mass spectrometry coupled with elevated energy technique. Issue 10 (May 2016) - Wang, Dandan; Qi, Meng; Yang, Qiming; Tong, Renchao; Wang, Rui; Bligh, S.W. Annie; Yang, Li; Wang, Zhengtao
Abstract : Plantaginis Semen is commonly used in traditional medicine to treat edema, hypertension, and diabetes. The commercially available Plantaginis Semen in China mainly comes from three species. To clarify the chemical composition and distinct different species of Plantaginis Semen, we established a metabolite profiling method based on ultra high performance liquid chromatography with electrospray ionization quadrupole time‐of‐flight tandem mass spectrometry coupled with elevated energy technique. A total of 108 compounds, including phenylethanoid glycosides, flavonoids, guanidine derivatives, terpenoids, organic acids, and fatty acids, were identified from Plantago asiatica L., P. depressa Willd., and P. major L. Results showed significant differences in chemical components among the three species, particularly flavonoids. This study is the first to provide a comprehensive chemical profile of Plantaginis Semen, which could be involved into the quality control, medication guide, and developing new drug of Plantago seeds.